The Application of Entrepreneurship and its Relationship to Improve Production and Success of Small Projects in the Kingdom of Saudi Arabia - Al-Juhaimi, Noura (The Arab Journal of Administration, 2023)
This study aimed to investigate the application of entrepreneurship and its relationship to improving productivity and the success of small projects in the Kingdom of Saudi Arabia. To achieve this objective, the descriptive approach was employed, and the study instrument consisted of a researcher-developed survey questionnaire. The questionnaire comprised two dimensions. The first dimension measured the current practice of entrepreneurship in small projects from the perspective of the employees, while the second dimension assessed the perceived impact of entrepreneurship on enhancing productivity and achieving the goals of small projects, also from the perspective of the employees. The study was conducted on a sample of 112 owners and employees of small projects in the Kingdom of Saudi Arabia, and they were stratified based on variables such as gender, project nature, and years of experience. The results revealed that the current application of entrepreneurship in small projects in the Kingdom of Saudi Arabia was perceived to be at a moderate level by the study sample. Moreover, the perceived impact of entrepreneurship on improving productivity and the success of small projects was considered to be high by the study participants. Additionally, the results indicated that there were no statistically significant differences in the responses of the study sample attributed to gender or project nature. However, differences were found in their responses based on years of experience, favoring those with higher years of experience. This was particularly evident in their perception of the current practice of entrepreneurship in small projects and its impact on enhancing productivity and achieving the goals of these projects.